Community contributing factors towards sustainable mobility in residential neighbourhood / Nurain Mohd Talmizi - Mohd Talmizi, Nurain (2018)
This purpose of this research is to evaluate the factors contributing to community behaviour towards neighbourhood’s sustainable mobility. A typical residential neighbourhood located in Section 7, Shah Alam is selected as a case study for the research. A total of one hundred and thirty-five completed questionnaires were collected from respondents from three residential types in the study area. Factor Analysis, specifically inferential analysis was employed to evaluate 15 items involved in measuring the three variables of intention, of which 5 items were excluded from the list due to their factor loading below 0.5. The first variable is Neighbourhood Street Connectivity (NSC) with five items; the second Neighbourhood Safety of Crime (NSoC) with three items and third is Neighbourhood Safety of Traffic (NSoT) with two items. Meanwhile, analysis was also conducted on nineteen items in measuring the three behaviour variables, where again nine items were excluded from the list due to their factor loading score of below 0.5. These variables and their associated items are Neighbourhood Security (NS) which has four items; Neighbourhood Infrastructure (NI) with three items; and Neighbourhood Aesthetic (NA) also with three items.